SurgiCal Obesity Treatment Study (SCOTS): a prospective, observational cohort study on health and socioeconomic burden in treatment-seeking individuals with severe obesity in Scotland, UK - Elizabeth Thompson; Ian Ford; David Beard; Nicola Greenlaw; Jennifer Logue; Mike Lean; Richard Welbourn; Abdulmajid Ali; Sally Stewart; Robert Lindsay; Bruce Tulloh; Jane Munro; et al. (BMJ Open)
Objectives There is a lack of evidence to inform the delivery and follow-up of bariatric surgery for people with severe obesity. The SurgiCal Obesity Treatment Study (SCOTS) is a national longitudinal cohort of people undergoing bariatric surgery. Here, we describe characteristics of the recruited SCOTS cohort, and the relationship between health and socioeconomic status with body mass index (BMI) and age.Participants/Methods 445 participants scheduled for bariatric surgery at any of 14 centres in Scotland, UK, were recruited between 2013 and 2016 for this longitudinal cohort study (1 withdrawal); 249 completed health-related preoperative patient-reported outcome measures. Regression models were used to estimate the effect of a 10-unit increase in age or BMI, adjusting for sex, smoking and socioeconomic status.Results Mean age was 46 years and median BMI was 47 kg/m2. For each 10 kg/m2 higher BMI, there was a change of −5.2 (95% CI −6.9 to –3.5; p<0.0001) in Rand 12-item Short Form Survey Physical Component Summary (SF-12 PCS), −0.1 (95% CI −0.2 to –0.1; p<0.0001) in EuroQoL 5-level EQ-5D version index score and 14.2 (95% CI 10.7 to 17.7; p<0.0001) in Impact of Weight on Quality of Life-Lite Physical Function Score. We observed a 3.1 times higher use of specialist aids and equipment at home (OR: 3.1, 95% CI 1.9 to 5.0; p<0.0001). Broadly, similar results were seen for each 10-year higher age, including a change of −2.1 (95% CI −3.7 to –0.5; p<0.01) in SF-12 PCS.Conclusions A higher BMI combined with older age is associated with poor physical functioning and quality of life in people seeking bariatric surgery treatment. Policy-makers must consider the health and care needs of these individuals and invest to provide increased access to effective weight management.Trial registration number ISRCTN47072588.